Intranasal Administration of 2/6-Rotavirus-Like Particles with Mutant Escherichia coli Heat-Labile Toxin (LT-R192G) Induces Antibody-Secreting Cell Responses but Not Protective Immunity in Gnotobiotic Pigs - Yuan, Lijuan; Geyer, Annelise; Hodgins, Douglas C.; Fan, Zhiqian; Qian, Yuan; Chang, Kyeong-Ok; Crawford, Sue E.; Parreño, Viviana; Ward, Lucy A.; Estes, Mary K.; Conner, Margaret E.; Saif, Linda J. (Journal of Virology, 2000)
Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI